Quantum Theory and Idealism - Boehmer, Stuart (European Journal of Applied Sciences, 2023)
We find that the Wigner Probability Distribution has a fully classical interpretation, and that the microscopic world is not a "black box" (per the Copenhagen Interpretation). Probability represents our state of knowledge of a system. However, in quantum theory, as opposed to classical theory, cause and effect is at the level of our state of knowledge, , not the state of the world, . Quantum theory is idealistic in the sense of Berkeley: the world is a conscious, shared hallucination.